Protein Enrichment Of Pycnoporus Sanguineus For Silver Nanoparticles Synthesis - Chan, Yen San (2014)
Controlling sizes of nanomaterials are attracting a great deal of attention because of their unit properties for achieving specific processes especially in biological and medical applications. In this context, Ag which possesses good antimicrobial effects is of interest. A simple and effective approach for the synthesis of Ag nanoparticles by reduction mechanism of proteins synthesized by several species of white rot fungi was studied. Pycnoporus sanguineus was found to produce smallest Ag nanoparticles with degree of monodispersity. A Box-Behnken design was employed to optimize a fermentation medium for the production of protein by the selected fungi. The four variables involved in the study were glucose, malt extract, yeast extract and pH. The optimized medium contained 8.39 gL-1, 18.34 gL-1, 14.71 gL-1 of yeast extract, glucose and malt extract respectively with initial pH 6.66; and produced the maximum protein at 0.858 gL-1. Kinetic growth of the fungi, glucose consumption and product formation of the tested fungus were also reported. It is showed that at initial glucose concentration of 20gL-1, Richard-modified logistic model (R2 =0.9839) for microbial growth, modified Gompertz model (R2 =0.9610) for product formation and first order non-growth associate (R2 =0.9736) for glucose consumption were fittd well with the experimental data. Sequential optimization strategy based on one-factor-at-a-time (OFAT) method and statistical experimental design were employed to optimize the process parameters for the enhancement of Ag nanoparticles synthesis. Based on the OFAT method, three significant factors influencing the size of Ag nanoparticles such as AgNO3 concentration, incubation temperature and agitation speed